PERSEPSI MAHASISWA TERHADAP METODE SIMULASI ONLINE TRADING DI BURSA EFEK INDONESIA DI FAKULTAS EKONOMI YOGYAKARTA - Sri Hermuningsih; Kristi Wardani (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2016)
ABSTRACTThis study aimed to investigate and analyze the students’ perceptions of the online tradingsimulation method in the Indonesia Stock Exchange. The research sample consisted of 100students of Faculty of Economics of Sarjanawiyata Tamansiswa University and students ofFaculty of Economics of Muhammadiyah University of Yogyakarta who became investors andwere active in trading. The analysis method was an independent test of mean difference.The results of the study showed that there was difference in perceptions between studentsof Faculty of Economics of Sarjanawiyata Tamansiswa University and students of Faculty ofEconomics of Muhammadiyah University of Yogyakarta regarding the online trading simultionmethod with a significance value of 0.004. This was caused by different behavioral intentionsbetween students of Faculty of Economics of Sarjanawiyata Tamansiswa University and studentsof Faculty of Economics of Muhammadiyah University of Yogyakarta in doing the online tradingsimulation, however the online trading simulation was joyful and effective for them to learn stockinvestment in the capital market.Keywords : persepsi, simulasi, online trading, Bursa Efek Indonesia